Shinderera - Perrault, Charles 1628-1703; McClintock, Barbara 1955- (Iwanami Shoten, 2015)
Although mistreated by her stepmother and stepsisters, Cinderella meets her prince with the help of her fairy godmother
Keywords: Fairy tales; Folklore / France; Folklore; France; Bilderbuch